The Role of Event Brand Awareness in Creating Event Brand Image, Event Brand Quality, and Revisit Intention (a Lesson from Ijen Car Free Day) - Parahiyanti, Cesya Rizkika; Hussein, Ananda Sabil (Jurnal Ilmiah Mahasiswa FEB, 2014)
Event industry currently is considered as one of interesting business opportunity in contributing major positive economic impact. Event could be categorized into some activities conducted by an event management or event organizer in  the case of achieving some specific outcomes. Specifically, the purpose of conducting an event is gathering people in a moment to do similar activity which leads to the formation of communities as part of social interaction in a society. Apart its role in creating communities, an event is also recognized as an essential marketing tool in branding of particular destination. This study aims to establish a theoretical event brand equity for which the key components of the brand equity were evaluated from visitor perspective  in the tourism context. Brand equity is constructed by four dimensions which are event brand awareness (EBA), event brand image (EBI), event brand quality (EBQ), and event revisit intention (ERI). By using convenience sampling, 205 visitors of Ijen Car Free Day (ICFD) as the event object were used as respondents to obtain the data. This study uses Partial Least Square (PLS) to analyze  the data both in outer model and inner model measurements. The finding of this study indicate that EBA has positive and significant influence to EBI, EBQ, and ERI. Then, EBI is also proven giving positive and significant influence to EBQ and ERI. In contrary, EBQ does not show significant influence to ERI.Keywords: EBA, EBI, EBQ, ERI